Level of waste management efficiency in the local government unit as perceived by the residents of Dolores, Eastern Samar. - Ayad, Veana Marie B. (Veana B. Marie Ayad [and] Kyrl Joyce B. Brozas, 2010)
Dolores is a third class municipality in the Province of Eastern Samar. Due to the continuing increase of its population, the waste generated in the municipality also increases. In line with this, it can be observed that there is no proper waste management in the municipality. Hence, it is for this reason that the researchers become interested in studying waste management efficiency in the Local Government Unit. This study is a descriptive-correlational research. It sought to determine the perception of the residents on the level of waste management efficiency in the Local Government Unit and how it is influenced by their demographic characteristics.